Sex Differences in Aggression Are Paralleled by Differential Activation of the Brain Social Decision-Making Network in Zebrafish - Scaia, María Florencia; Akinrinade, Ibukun; Petri, Giovanni; Oliveira, Rui F. (Frontiers in Behavioral Neuroscience, 2022)
Although aggression is more prevalent in males, females also express aggressive behaviors and in specific ecological contexts females can be more aggressive than males. The aim of this work is to assess sex-differences in aggression and to characterize the patterns of neuronal activation of the social-decision making network (SDMN) in response to intra-sexual aggression in both male and female zebrafish. Adult fish were exposed to social interaction with a same-sex opponent and all behavioral displays, latency and time of resolution were quantified. After conflict resolution, brains were sampled and sex-differences on functional connectivity throughout the SDMN were assessed by immunofluorescence of the neuronal activation marker pS6. Results suggest that both sexes share a similar level of motivation for aggression, but female encounters show shorter conflict resolution and a preferential use of antiparallel displays instead of overt aggression, showing a reduction of putative deleterious effects. Although there are no sex-differences in the neuronal activation in any individual brain area from the SDMN, agonistic interactions increased neuronal activity in most brain areas in both sexes. Functional connectivity was assessed as co-activation matrices of the SDMN, showing that winning increases functional connectivity throughout the SDMN in both sexes while it is reduced as a consequence of social defeat in males, suggesting a distinct neural activation pattern associated to social experience during fights. Functional connectivity also shows positive co-activation throughout the SDMN in females and negative associations in males, suggesting sex-differences in the brain excitatory-inhibitory balance of the SDMN. Results also show a higher integration of the SDMN in females than males and that the most influential nodes in each network are different across social treatments in a sex-specific manner, suggesting a sex-specific differential activation of the social brain as a consequence of social experience. Overall, our study adds insights into sex-differences in agonistic behavior and on the neuronal architecture of intrasexual aggression in zebrafish.